Chemistry experimentation skill grade 9 & 10 (supplementary reading material) - Iqtidar ud din muhammad (Islamabad National book foundation, 2024)
This supplementary material aims to build practical laboratory skills in Chemistry for students of Grades 9 and 10. It covers basic lab techniques, safe handling of chemicals, accurate measurement methods, and experimental procedures. Students learn to perform experiments related to topics like acids and bases, chemical reactions, and separation techniques. The material emphasizes observation, data recording, analysis, and drawing scientific conclusions, helping students connect theoretical knowledge with hands-on practice through the scientific method.